Compact UWB CPW-fed Monopole Antenna with Variable Triple-band-notched Property. Issue 4 (4th July 2021) - Asadpor, Loghman; Rezvani, MirHamed
Abstract : In this paper, a modified compact ultra-wide band (UWB) monopole antenna possessing U-shaped slots and multi-band rejection characteristics are presented. The dimensions of the presented antenna are 30 × 30 × 1 mm 3, and it is fed by the coplanar waveguide (CPW). Inverted U-shaped slots produce three notched frequency bands at 2.5, 3.5 and 5.5 GHz. The lengths of the slots are modified for adjusting the frequency bands. The results of measurement and simulation show a VSWR of ≤2 for the antenna. The presented antenna is a perfect candidate for applications in UWB because of its omnidirectional radiation patterns. The antenna shows a radiation efficiency of above 85%.